PENGARUH TOTAL HUTANG, VOLUME PENJUALAN, TOTAL AKTIVA DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH - Simorangkir, Else Rohayu; Sitanggang, Tina Novianti; Parapat, Dini Dargita Marlina; Harianja, Hotriado (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
The aim of this research is to determine the effect of total debt, sales volume, total activities, and operational costs on net profit. The object of this research is a coal sub-sector mining company listed on the Indonesia Stock Exchange for the 2019-2023 period. This research uses quantitative methods with secondary data obtained from company financial reports. The population of this study was 16 companies with a sampling technique using purposive sampling so that 12 companies met the criteria within a period of 5 years. The data analysis used is multiple linear regression analysis using SPSS version 26 tools. The results of this research show that simultaneously total debt, sales volume, total assets, and operational costs have an effect on net profit. Partially, sales volume has a positive and significant effect on net profit, while total debt, total assets, and operational costs have no effect on net profit. With an Adjusted R Square value of 0.73, which means that the contribution of all independent variables influences the dependent variable by 73% and the remaining 27% is influenced by other variables. The conclusion from the results of this research is that of the 4 variables tested, there is 1 variable, namely sales volume which influences net profit.